2010
DOI: 10.4269/ajtmh.2010.09-0608
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of 56-kDa Type-Specific Antigen Gene of Orientia tsutsugamushi Isolates in Taiwan

Abstract: Scrub typhus is a rickettsial disease transmitted to humans through the bite of chigger mites infected with Orientia tsutsugamushi, and is an endemic disease in Taiwan. To elucidate the molecular epidemiology of O. tsutsugamushi, the complete open reading frame of the 56-kDa type-specific antigen gene sequence of strains isolated from scrub typhus patients were determined and analyzed. A total of 116 isolates of O. tsutsugamushi were successfully isolated from patients infected in diverse geographic origins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…Consistently, a large number of isolates belonged to the TA763 clade, a strain type commonly present in Thailand but not in Japan and Korea. It is noteworthy that the 56-kDa TSA gene sequences detected in this study were closely related to those found in a previous study of blood samples from Taiwan scrub typhus patients (15), suggesting the pathogenic potential of O. tsutsugamushi strains. The results are shown in Table 2, indicating that among Kato-related strains, KM-06, KM21-1 OI-09, and TT01-1 were 99% or more identical to the TW-22 strain.…”
Section: Resultssupporting
confidence: 64%
“…Consistently, a large number of isolates belonged to the TA763 clade, a strain type commonly present in Thailand but not in Japan and Korea. It is noteworthy that the 56-kDa TSA gene sequences detected in this study were closely related to those found in a previous study of blood samples from Taiwan scrub typhus patients (15), suggesting the pathogenic potential of O. tsutsugamushi strains. The results are shown in Table 2, indicating that among Kato-related strains, KM-06, KM21-1 OI-09, and TT01-1 were 99% or more identical to the TW-22 strain.…”
Section: Resultssupporting
confidence: 64%
“…Previously, Tamura et al described six prototype genotype strains: Karp, Kato, Kuroki, Kawasaki, Gilliam and Shimokoshi [3], [10], [11], [12], [13], [17]. Six different Taiwanese genotyping isolates were also characterized by RFLP analysis by Taiwan CDC in 1999: Taiwan-A, -B, -C, -D, -E and -F [21].…”
Section: Resultsmentioning
confidence: 99%
“…A recent phylogenetic analysis of O. tsutsugamushi from Taiwan reported two unique sequence types along with Karp-related, Saitama, JG-related, and Kuroki-related genotypes. 12 Multi-locus sequence typing (MLST) analysis of Thai isolates has shown a very high rate of recombination, which along with gene duplication and horizontal transfer accounts for the genetic diversity among O. tsutsugamushi isolates. 13,14 In 2008, five O. tsutsugamushi clades were reported to be circulating in Cambodia and three in Vietnam, with high genetic diversity.…”
mentioning
confidence: 99%